أثر مهارات التفاعل في تحسين رضا المرضى عن جودة الخدمات الصحية دراسة تطبيقية على المؤسسات الصحية في مدينة الخمس – ليبيا (Comprehensive Journal of Science, 2025)
study explores the role of interaction skills in enhancing patients' perceptions of the quality of healthcare services provided in private healthcare institutions in Al-Khums. The aim is to assess the impact of effective communication skills, empathy, active listening, and clarity of information on improving patient satisfaction and the quality of care provided. Data were collected through questionnaires distributed to a sample of patients receiving healthcare services in these institutions, and the results were analyzed using appropriate statistical methods.The findings revealed a statistically significant positive relationship between interaction skills and patient satisfaction with healthcare services. The study highlighted that effective communication and empathy significantly enhance patients' feelings of being cared for, positively affecting their overall healthcare experience. Additionally, active listening impacted patient satisfaction by addressing concerns and fostering trust and support during care. This underscores the importance of providing clear, understandable information to improve patient experience.The study recommends developing training programs to improve empathy and active listening skills among healthcare providers and offering clear, accurate information to patients about their health and treatment plans. Furthermore, it suggests enhancing the technical aspects of healthcare services, focusing on medical and technical competence to ensure the delivery of high-quality care.
Keywords: Interaction skills, healthcare service quality, effective communication, empathy, active listening, clarity of information.